2019
DOI: 10.3390/ijms20030683
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Platelet-Rich and Platelet-Poor Plasma on Endogenous Mechanisms of Skeletal Muscle Repair/Regeneration

Abstract: The morpho-functional recovery of injured skeletal muscle still represents an unmet need. None of the therapeutic options so far adopted have proved to be resolutive. A current scientific challenge remains the identification of effective strategies improving the endogenous skeletal muscle regenerative program. Indeed, skeletal muscle tissue possesses an intrinsic remarkable regenerative capacity in response to injury, mainly thanks to the activity of a population of resident muscle progenitors called satellite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 167 publications
0
80
0
3
Order By: Relevance
“…In recent years, great attention has been paid to the identification of new therapeutic agents and treatments that may promote the repair/regeneration of damaged skeletal muscle. In such a context, several in vitro and in vivo studies provided evidence supporting the advantage of the use of PRP for muscle regenerative purpose [30,66]. In this line, we have recently demonstrated the capability of PRP to either stimulate proliferation and differentiation of myogenic progenitors, including satellite cells [58], or prevent the TGF-β1 induced differentiation of fibroblasts towards myofibroblasts [48,57].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In recent years, great attention has been paid to the identification of new therapeutic agents and treatments that may promote the repair/regeneration of damaged skeletal muscle. In such a context, several in vitro and in vivo studies provided evidence supporting the advantage of the use of PRP for muscle regenerative purpose [30,66]. In this line, we have recently demonstrated the capability of PRP to either stimulate proliferation and differentiation of myogenic progenitors, including satellite cells [58], or prevent the TGF-β1 induced differentiation of fibroblasts towards myofibroblasts [48,57].…”
Section: Discussionmentioning
confidence: 83%
“…In this regard, Platelet-Rich Plasma (PRP)-defined as a plasma fraction with a concentration of platelets above baseline levels and representing a source of numerous biologically active molecules-may offer promising perspectives [30]. Indeed, many in vitro and in vivo studies have demonstrated the anti-fibrotic potential of this blood product in different tissues [31][32][33][34][35][36][37][38], including skeletal muscle [30,[39][40][41][42][43][44][45][46], and have indicated the fibroblast-myofibroblast transition as the cell process target of its action [31][32][33]36,38,44,47,48]. Furthermore, the positive contribution of PRP to skeletal muscle regeneration has been demonstrated either in vivo or in vitro, thanks to its capability to promote the myogenic program [30].…”
Section: Prp As An Anti-fibrotic Agentmentioning
confidence: 99%
“…There is a growing consensus for the positive effects of PRP as an adjuvant therapy to aid the healing of surgical wounds and injuries. In fact, the growth factors present in PRP are involved in every stage of wound healing [71][72][73] , and several reviews [74][75][76][77][78] , systematic reviews [79][80][81] , and clinical studies [82][83][84] have reported their involvement in enhanced soft-tissue healing outcomes. Our results did not show statistically significant differences in the SWAS scores between the groups because they both obtained the best possible score.…”
Section: Discussionmentioning
confidence: 99%
“…Pain relief with PRP is reported in patients with skeletal muscle injuries and strains [35][36][37]. ere is also evidence for reduction of inflammation and size of fibrotic scars with PRP in skeletal muscle injury [38].…”
Section: Discussionmentioning
confidence: 94%